DIAGNOSTIC FEATURES OFSPEECH DISORDERS IN CANCER PATIENTS WITH ACQUIRED MAXILLARY DEFECTS - I. S. Korzhov (Сибирский онкологический журнал, 2016)
The review describes the mechanisms of speech production, the causes and characteristics associated with impaired speech in patients with acquired maxillar defects. The use of diagnostic sounds specific for patients with acquired maxillar defects is justified in order to control the quality of the reconstructed speech. Timbre, acoustic characteristics of vowels, as well as expert evaluation of objective parameters of speech can not serve as the basic factors of the quality of the reconstructed speech. In contrast, the criteria for formal evaluation of speech quality are the changes in the frequency range of sounds, occurrence or loss of certain formants and the change in time of the overall tone sounds and phonemes. Подобные изменения легко фиксируются такими инструментальными средствами, как спектральный анализ и анализ амплитудограммы. For objective research it is necessary to use two letter sounds composed of vowels and consonants, allowing diagnostic sounds in the context to be studied, however, the effects of coarticulation and prosody are minimized. The use of formal features of specific sounds allows the subjective assessment of speech quality to be minimized.